FAMILY QUALITY OF LIFE: CONTENT VALIDITY OF A TOOL FOR FAMILIES OF ADULTS WITH INTELLECTUAL DISABILITIES IN BRAZIL - BİTENCOURT, Daniela and GRàCİA, Marta and BELTRAN, Francesc (The Eurasia Proceedings of Educational and Social Sciences, 2015)
On an international level, studies on the quality of life (QOL) are becoming more and more frequent, and few of them focus on the study of the quality of life of people with DI and their families. All of these studies identify a number of fields or areas that define the QoL, on both individual and family levels (Brown, MacAdam-Crisp, Wang, & Iarocci, 2006; Turnbull, Brown, & Turnbull, 2004; Schalock et al., 2002). In Brazil, legal guidelines exist that are moving relatively forward with respect to people with disabilities. However, in spite of all of the legislation and benefits, the insertion or inclusion of people with disabilities in the job market, schools and leisure centers is still low. The aim of the current research is to present the translation, adaptation and content validation of the Beach Center Family Quality of Life (Summers, Poston, Turnbull, Marquis, Hoffman, & Mannan, 2005) in the Brazilian context. To carry out the adaptation and standardization of the scale the seven steps proposed by Tassé and Craig (1999) and Beaton, Bombardier, Guillemin and Ferraz (2000) will be followed: (1) translation/adaptation to Portuguese; (2) consolidation of translation/adaptation; (3) preliminary normalization of translation; (4) review/adjustments; (5) pilot test of translation; (6) revision/adjustment of translation; (7) standardization the scale and obtaining index of validity and reliability. The research is currently on Step 4, review/adjustments, in which the content validity is implemented in order to achieve semantic, conceptual, idiomatic and experimental equivalence between the original tool and the final one (Tassé & Craig, 1999; Beaton et al., 2000). It is important to mention that the aim of the research is to understand the family quality of life, not only of the person with intellectual disabilities, but those of all of their family members.